The Effect of Certification and Product Knowledge on Instant Food Purchasing Decisions through Halal Awareness: The Moderating Role of Religiosity - Zamratul Akbar; Agustina Shinta Hartati Wahyuningtiyas; Riyanti Isaskar (Journal of Consumer Sciences, 2025)
Background: Digital transformation and the implementation of advanced technologies play a crucial role in the advancement of the halal industry. As a strategic step in building a halal product ecosystem, developing halal food products, encompassing the entire supply chain from upstream to downstream, is essential. However, there are many halal products, particularly food products, whose halal status is not guaranteed and lack halal certification. BPJPH (Halal Product Assurance Organizing Agency) reported that around 1,544 products had not received halal certification, including 192 ready-to-eat instant foods registered as halal. Purpose: In light of these issues, this research examines how halal certification and knowledge of halal products affect instant food purchase decisions through halal awareness moderated by religiosity. Methods: This study employed a cross-sectional design with a non-probability sampling approach, specifically the convenience sampling technique. Data was obtained using questionnaires distributed to 150 respondents who have consumed instant food. Using WarpPLS 8.0, the data was analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). Findings: The research findings indicate that halal certification and knowledge of halal products significantly impact halal awareness and instant food purchase decisions. Halal awareness also mediates the effect of halal certification and knowledge of halal products on purchase decisions. Furthermore, religiosity strengthens the relationship between halal awareness and individuals’ decision to purchase instant food in Malang. This study provides valuable insights into instant food purchase decisions, particularly for halal instant food. Conclusion: Based on these results, it is recommended that producers develop marketing strategies that emphasize halal certification or logos and provide clear information regarding the benefits of halal products. Research implication: Companies should collaborate with authorized institutions and religious figures to increase societal halal awareness. Meanwhile, LPPOM MUI should simplify the halal certification process, launch campaigns to raise awareness about the importance of halal products, and provide the general public comprehensive education about halal concepts.